Thermal Effects. (1st October 2017) - Xu, Dong; Zhang, Panyue; Ye, Jie; Zhang, Haibo; Liu, Jianbo; Yan, Li; Wang, Bei; Huang, Xiaoding; Zeng, Guangming
Abstract : This review focuses on the research literatures published in 2016 relating to thermal effects in water pollution control. This review is divided into five sections: biological nitrogen removal, organic pollutant degradation, resource recovery, pretreatment and anaerobic digestion, microbial community.